Effects of Replacing Medical Zinc Oxide with Different Ratios of Inorganic: Organic Zinc or Reducing Crude Protein Diet with Mixed Feed Additives in Weaned Piglet Diets - Han Jin Oh; Myung Hoo Kim; Min Ho Song; Ji Hwan Lee; Yong Ju Kim; Se Yeon Chang; Jae Woo An; Young Bin Go; Dong Cheol Song; Hyun Ah Cho; Min Ji Kim; Hyeun Bum Kim; et al. (Animals, 2021)
One hundred twenty weaned piglets (9.34 ± 0.74 kg) were used in a four-week experiment to investigate the effects of replacing medical ZnO with a different ratio of inorganic and organic zinc (IZ:OZ) or a low-crude-protein diet (LP) with mixed feed additives (MFAs) in the weaned piglets’ diet. The dietary treatments included a control (CON), T1 (T1; ZnO 1000 mg/kg), T2 (IZ:OZ 850:150), T3 (IZ:OZ 700:300), T4 (IZ:OZ, 500:500), and T5 (LP with MFAs (0.1% essential oils + 0.08% protease + 0.02% xylanase)). The growth performance was decreased (p < 0.05) in the CON treatment compared with the T4 treatment. The diarrhea incidence was decreased (p < 0.05) in the T4 and the T5 treatment compared with the CON and the T1 treatments. The apparent total tract digestibility (ATTD) of nutrients were increased (p < 0.05) in the T4 and T5 treatments compared with the CON, T1, and T2 treatments. The T4 treatment had a higher (p < 0.05) ATTD of zinc than the T1, T2, and T3 treatments. The fecal microflora was improved (p < 0.05) in the T5 treatment compared with the CON and T3 treatments. In conclusion, IZ:OZ 500:500 could improve growth performance, nutrient digestibility, and zinc utilization while reducing diarrhea incidence in weaned piglets. Moreover, LP with MFA could replace medical ZnO.